Geomagnetic observations and models - Mandea, Mioara; Korte, Monika (IAGA Special Sopron Book Series, 2011)
This volume provides comprehensive and authoritative coverage of all the main areas linked to geomagnetic field observation, from instrumentation to methodology, on ground or near-Earth. Efforts are also focused on a 21st century e-Science approach to open access to all geomagnetic data, but also to the data preservation, data discovery, data rescue, and capacity building. Finally, modeling magnetic fields with different internal origins, with their variation in space and time, is an attempt to draw together into one place the traditional work in producing models as IGRF or describing the magnetic anomalies. Audience: This book will be of interest to researchers and scientists in geophysics and geomagnetism.